2012
DOI: 10.1038/clpt.2012.184
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the CYP4F2 p.V433M Polymorphism on Coumarin Dose Requirement: Systematic Review and Meta-Analysis

Abstract: A systematic review and a meta-analysis were performed to quantify the accumulated information from genetic association studies investigating the impact of the CYP4F2 rs2108622 (p.V433M) polymorphism on coumarin dose requirement. An additional aim was to explore the contribution of the CYP4F2 variant in comparison with, as well as after stratification for, the VKORC1 and CYP2C9 variants. Thirty studies involving 9,470 participants met prespecified inclusion criteria. As compared with CC-homozygotes, T-allele c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 50 publications
2
45
1
2
Order By: Relevance
“…To the best of our knowledge, this is the first study to explore the association between CYP4F2 and the warfarin stable dose solely for the Asian population. As opposed to the studies by Danese et al (16) and Liang et al (17), a statistical difference was observed between the CT and TT genotype, which may be an indication of a larger effect of CYP4F2 on the warfarin dose in the Asian population.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to explore the association between CYP4F2 and the warfarin stable dose solely for the Asian population. As opposed to the studies by Danese et al (16) and Liang et al (17), a statistical difference was observed between the CT and TT genotype, which may be an indication of a larger effect of CYP4F2 on the warfarin dose in the Asian population.…”
Section: Discussioncontrasting
confidence: 53%
“…However, the findings are inconsistent, particularly for Asian patients (10)(11)(12)(13)(14)(15). In 2012, two results of meta-analyses showed that the CYP4F2 gene polymorphism was associated with the CYP4F2 gene polymorphisms on the warfarin maintenance dose: A systematic review and meta-analysis XUE SUN 1,2 , WAN-YING YU 1,2 , WAN-LE MA 1 , LI-HUA HUANG 3 and GUO-PING YANG warfarin maintenance dosage (16,17). However, as they all focused on the studies of European and American populations, the impact of the CYP4F2 genotype on warfarin dose in the Asian population has not been investigated adequately.…”
Section: Introductionmentioning
confidence: 99%
“…CYP4F2 contributes to vitamin K1 oxidation, and some variants could result in reduced enzyme activity [79] . An association between the CYP4F2 variant (rs2108622) and warfarin dose was subsequently confirmed in a meta-analysis involving more than 9000 participants from 30 studies [80] . Although the association of CYP4F2 is significant, the effect size is much lower than those contributed of VKORC1 and CYP2C9 in Han Chinese in South China [81] , and its clinical use …”
Section: Warfarinmentioning
confidence: 90%
“…Since Caldwell et al reported the clinical impact of the CYP4F2 genotype [20], several studies have confirmed that the CYP4F2 polymorphism is associated with warfarin dosage [22,24]. However, earlier studies have reported a lower contribution of the CYP4F2 polymorphism to dosage variability than that by the VKORC1 and CYP2C9 polymorphisms [26]. Harada et al reported that the Japanese patients with CYP4F2 TT genotype required approximately 1.2-fold warfarin maintenance dose compared to those with the CC and CT genotypes, a result that is similar in the present study; however, no significant association between the CYP4F2 genotypes and warfarin maintenance dose was observed [23].…”
Section: Discussionmentioning
confidence: 93%
“…However, some studies have also demonstrated that the effect of the CYP4F2 rs2108622 polymorphism on warfarin response is nonsignificant [23][24][25]. In addition, a recent meta-analysis on the impact of the CYP4F2 polymorphism on coumarin dose requirements suggests a lower contribution of this polymorphism than that of the VKORC1 and CYP2C9 polymorphisms [26].…”
Section: Introductionmentioning
confidence: 96%